Response of germination, growth and yield of okra (ABELMOSCHUS ESCULENTUS) to seed priming duration and p-sources in Northwest Pakistan - Shah, Abdul Raziq; Sajid, Muhammad; Rab, Abdur-; Ara, Neelam; Ahmad, Masood; Wahid, Fazal-i-; Shafi, Gohar (Global Journal of Food and Agribusiness Management, 2012)
An experiment was conducted at Horticulture Research Farm, KPK Agricultural University Peshawar during summer 2008 to evaluate the response of okra to phosphorus sources and soaking durations. The experiment was laid down in randomized block design with three replications. Four priming sources that is, distilled water, Diammonium phosphate (DAP), single super phosphate (SSP), SSP + Na2CO3 and 4 h durations up to 48 h seed soaking along with un-primed seed were studied. The results indicated that higher germination percentage (85.94%), survival percentage (94.05%), plant height (138.97 cm), number of leaves (26.69), pods (31.01) and seeds pod-1 (49.52), pod length (10.99 cm), pod yield (2702.69 kg ha-1 ), early emergence (7.79) and flowering (33.65) was observed in plots in which seed soaked with SSP solution was used. The highest plant weight (433.36 g) was observed in plots in which seed soaked with DAP was used. Mean values of interactions result showed that the highest number of leaves (36.13) and pods plant-1 (45.26), and pod yield (5063.53 kg ha-1 ) was produced in plots in which seeds were soaked for 24 h in SSP solution. Lengthy pods (12.60 cm) was noted with seeds soaked for 24 h in DAP solution. Number of seeds pod-1 (63.06) reached maximum when seeds were soaked for 20 h in SSP solution. The SSP solution performed best in most of the parameters while distilled water showed poor performance. It is concluded from the experiment that soaking okra seeds with SSP solution for 24 h could improve germination, stand establishment, growth and yield of okra in the study area.